REPRODUCTION OF SPACE: ÜÇKUYULAR MARKET UNDER VIADUCT - GELİŞKAN , Nil Nadire (SSD Journal, 2022)
Lefebvre defines markets as places of exchange where people and goods come face to face and also underlines that the market has had a central position throughout history which shapes gathering place. (Lefebvre, 2011) Üçkuyular market places, which was taken under viaduct around 2016, is an important center of İzmir which takes place every Sunday and becomes specialized with fresh fruits and vegetables selling including other fields (clothing, charcuterie, fish market). Strategically markets establish at reachable points with both vehicle and foot. Üçkuyular as a region serves transfer center for metro, bus, ferry, dolmush for districts and tram in the near future. However, with sudden decision of municipality location of Üçkuyular market will move from its place to under viaducts of highway. In this paper, it is aimed to examine how these kinds of decisions were taken free from users with ignoring “right to the city”